A new pricing strategy evaluation model. (2017) - Baker, Timothy; Collier, David; Jayaraman, Vaidy
Academics and practitioners agree that better pricing strategies are important drivers of return on investment (ROI), yet this premise has not been fully tested. We develop a new pricing adherence fraction (PAF) and then investigate whether it is related to changes in return on investment for a firm's products. We test this PAF-ROI performance relationship using ten pricing strategies defined and quantified by Noble and Gruca (1999) using logit modelling and regression analyses. Survey results of 385 durable capital goods manufacturers in business-to-business (B2B) markets provide the data for this research. A statistically significant PAF-ROI relationship is found between using the best pricing strategy for a given pricing situation and an increased return on an investment. Confidence interval analysis reveals that pricing mistakes can cost firms up to a 10% decrease in ROI. The PAF methods and procedures for a particular pricing situation allow a current pricing strategy to be compared systematically to the best pricing strategy among ten possible pricing strategies.